Whole rock major, minor, and trace element compositions of basaltic glassy pillow selvages and hyaloclastite from Kverkfjöll, Iceland. - Iðunn Kara Valdimarsdóttir (Zenodo, 2023)
Whole rock compositions of glassy pillow selvagesand hyaloclastite (tuff)from the Kverkfjöll region, Iceland, were measured as a part of a master's thesis in geology from the University of Iceland.Major and minor element compositions for the glassy selvages were measured via ICP-OES. Trace element compositions for the glassy selvages and tuff were measured via ICP-MS.Please refer to the actual thesis for more information: Valdimarsdóttir, I. K. (2023). Origin, extent, and emplacement conditions of newly exposed pillow lavas in the Kverkfjöll region, Iceland . [Master's thesis, University of Iceland]. Skemman.